The role of indigenous fruit trees in the rural livelihoods : a case of the Mwekera area, Copperbelt province, Zambia - Kalaba, Felix Kanungwe (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Forest and Wood Science))—University of Stellenbosch, 2007.